2011
DOI: 10.1371/journal.pone.0020918
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies against Accumulation-Associated Protein Affect EPS Biosynthesis and Enhance Bacterial Accumulation of Staphylococcus epidermidis

Abstract: Because there is no effective antibiotic to eradicate Staphylococcus epidermidis biofilm infections that lead to the failure of medical device implantations, the development of anti-biofilm vaccines is necessary. Biofilm formation by S. epidermidis requires accumulation-associated protein (Aap) that contains sequence repeats known as G5 domains, which are responsible for the Zn2+-dependent dimerization of Aap to mediate intercellular adhesion. Antibodies against Aap have been reported to inhibit biofilm accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 41 publications
(76 reference statements)
2
28
0
1
Order By: Relevance
“…3 and 4) and SesC (Fig. 4); this phenomenon has been documented previously for Aap (16). Antibodies to EmbP performed well in the prophylactic assay (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…3 and 4) and SesC (Fig. 4); this phenomenon has been documented previously for Aap (16). Antibodies to EmbP performed well in the prophylactic assay (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Proteins were expressed in Escherichia coli BL21(DE3) using Overnight Express Autoinduction System 1 (EMD Millipore), per the manufacturer's protocol. For Aap/SERP2398, a 20-amino-acid peptide (PGKPGVK NPDTGEVVTPPVD) was synthesized for immunization (GenScript), based on its published identification as an antibiofilm epitope (16). Expression cultures were harvested by centrifugation, and cell pellets were stored at ÏȘ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, the rod-like structure might play a role in maintaining bacterial separation in the biofilm. Furthermore, a recent study on Aapmediated biofilm formation by S. epidermidis showed that anti-G5 monoclonal antibodies enhanced bacterial accumulation, whereas those with an epitope in the E segment inhibited biofilm accumulation to 60% of the maximum (42). This suggests that G5 and E domains might play different roles during bacterial accumulation, despite their structural similarity.…”
Section: Discussionmentioning
confidence: 98%
“…Previous investigations have demonstrated that Aap domain architecture and subsequent processing is variable among clinical and laboratory strains (12,26,33,35,39). Draft genomic sequencing revealed that Aap of 1457 has an A domain with 11 short, 16-aa repeats, followed by the conserved L-type lectin domain, while the B domain contains 6 full and 1 partial B repeat followed by 2 putative collagen-like repeat motifs.…”
Section: S Epidermidis Strain 1457 Produces and Processes Aap In Vitromentioning
confidence: 99%
“…Clearly, additional molecules are capable of supporting biofilms in vivo. Among these, Aap is the most well studied and frequently identified component of PIA-independent, protein-mediated S. epidermidis biofilms (12,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Aap is a cell wall-anchored protein (41) of approximately 220 kDa; however, the size varies between strains due to differences in the number of B domain repeats (Fig.…”
mentioning
confidence: 99%